A NEW MODEL FOR HEAD LOSS ASSESSMENT OF SCREEN FILTERS DEVELOPED WITH DIMENSIONAL ANALYSIS IN DRIP IRRIGATION SYSTEMS1. (7th May 2014) - Wu, Wenyong; Chen, Wei; Liu, Honglu; Yin, Shiyang; Niu, Yong
ABSTRACT This study is based on data of the hydraulic analysis of 15 types of screen filters, incorporating such technical parameters as the pipe inlet/outlet inner diameter Dp, angle between filter body and inlet/outlet a, filter pore diameter ds, filter mesh number M, water velocity of inlet/outlet vi, and average water velocity of filter pore vm to develop a dimensional head loss model. The regression coefficient <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fcqk27n" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Radj2</alternatives> is 0.951 and the correlation coefficient R between the measured value and predicted value is 0.97. Using the model to study filter head loss variations as different structure parameters change, and the variation of structure parameters would lead to the changes of vi, vm, Re and Fr, consequently resulting in head loss variation. It was found that the head loss decreases significantly as the inlet/outlet diameter and filter mesh diameter decrease. An increasing angle or filter mesh size (while keeping the filter diameter constant) does not have a significant impact on the screen filter head loss. For the screen filter structural design, the proper inner diameter of inlet/outlet and filter mesh diameter should be selected to reduce both water head loss along the path and local head loss. Copyright © 2014 John Wiley & Sons, Ltd.